Investigating the Best Time of Weight Bearing After Anterior Cruciate Ligament Reconstruction (Immediate or Delayed): A Randomized Clinical - Mohsen Mardani-Kivi; Sina Kamrani Moghadam; Amin Izadi; Ehsan Kazemnejad Leili; Kamran Asadi (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Postoperative rehabilitation protocols, such as immobilization and non-weight-bearing periods during the acute phase after anterior cruciate ligament (ACL) surgery vary depending on the surgeon or the institution and lack clear standardization. Weight bearing (WB) after ACL reconstruction (ACLR) is critical. This study compares the results of WB immediately after surgery and partial WB with a brace after ACLR. Materials & Methods In this randomized clinical trial, the block random sampling method was used to select 84 patients who were divided into two groups. Group 1 was allowed to have full WB after surgery and Group 2 was asked to use braces after surgery, and they were divided into partial WB for one month and then full WB. Meanwhile, demographic information was recorded. The Lachman test, anterior knee pain, and kneeling pain before and one month after the surgery were also recorded. Knee function was evaluated using the international knee documentation committee, knee injury and osteoarthritis outcome score, and Lysholm scales before surgery and 1, 3, and 6 months after surgery. The data were analyzed using the SPSS software, version 20, and the Fisher exact test, the chi-square test, the Friedman test, and repeated measures analysis of variance. Results Most of the patients were men under 30 years of age. There was no statistically significant difference in the demographic information of the patients in the two groups. Kneeling pain, anterior knee pain, and the Lachman test did not differ between the two groups one month after the surgery. There was no difference between the two groups in the scores using the international knee documentation committee, knee injury and osteoarthritis outcome score, and Lysholm score in the 6-month follow-up. All the examined indicators in each group improved over time. Conclusion WB immediately after surgery compared to partial WB at 1, 3, and 6 months after ACLR do not differ; therefore, patients can bear full weight if they tolerate it.